Governmental accounting innovation in Yemen : the introduction of accruals accounting & the moderating role of e-government / Abdulla Mohamed Hamoud Al-Tholaya - Al-Tholaya, Abdulla Mohamed Hamoud (2013)
The adoption of accrual basis of accounting by governments is an important element to transform the bureaucratic administrative cash-based system to a more informative financial management system to ensure the supply of comprehensive, reliable, and meaningful financial information for appropriate accountability and decision making. Yemen is engaged in such reform, with advent of the E-Government, Information and Telecommunication Technologies era. This study describes the Yemen Central Government’s accounting and reporting system, its institutional framework, its policy characteristics and the environmental conditions that are in favour and unfavourable of such reform change. It also investigates the relationships between attitudes, innovative and organisational factors, as well as the adoption of accrual basis of accounting barriers and its implementation. Additionally, it investigates the moderating effects of E-Government between the abovementioned relationships during the face of change. This is to test if E-Government interaction will influence the strength and direction of the mentioned relationships in the model, and if the predictive power of that model would be increased. Finally, it examines the feasibility of accrual basis of accounting in Yemen. This study applied multiple theories, multi-method approaches (mixed-methods), and utilised qualitative and quantitative methodologies for data (analysis), collected from questionnaires and interview surveys. Twenty hypotheses are tested. The findings show that innovative and organisational factors have a positive relationship with an attitude toward change, while barriers have a negative relationship with an attitude toward change, but E-Government has a positive relationship with an attitude toward change. The results show that institutional frameworks such as the current Yemen governmental accounting and reporting framework, have an acceptable level of moving towards accrual basis of accounting, while accounting system objectives and reporting policy specifications reveal acceptable level of objectives and insufficient level of reporting policy. Even though the Yemen government officially announced the adoption of accrual basis of accounting and performed several alterations on the accounting system toward accrual basis, central government accounting officials are still using (modified) cash basis accounting. Computer integration, across governmental departments, is not complete. Environmental factors that contributed to change from cash basis to accrual basis of accounting are reform stimuli, pressures related to other reforms, and forces of globalisation. The contextual variables are in favour of moving toward accrual basis of accounting. Attitudes toward change were found to have a full mediation effect between innovation factors, organisational factors, barriers, and E-Government, emphasising the important role of accountants, financial managers, and others in the feasible adoption and implementation of accrual basis of accounting. E-Government shows a moderating effect on the relationships between all independent variables and the mediating variable of attitude toward change. This study found Government officials' attitude toward change from cash basis accounting to accrual basis of accounting to be very critical for the adoption and implementation of such change. Government financial officials have to be in line with the change process and their support is crucial for a successful adoption. E-Government (capabilities) is an important element in the success of the adoption and implementation of accrual basis of accounting.